The economics of gambling - Vaughan Williams, Leighton (London ; New York : Routledge, 2003)
This book is a timely collection of works by well-proven, first rate researchers in the economics of horse race and sports wagering, and other forms of gaming.
Introduction / Leighton Vaughan Williams -- The favourite-longshot bias and the Gabriel and Marsden anomaly: an explanation based on utility theory / Michael Cain, David Peel and David Law -- Is the presence of inside traders necessary to give rise to a favorite-longshot bias? / Adi Schnytzer and Yuval Shilony -- Pari-mutuel place betting in Great Britain and Ireland: an extraordinary opportunity / David Jackson and Patrick Waldron -- Betting at British racecourses: a comparison of the efficiency of betting with bookmakers and at the Tote / John Peirson and Philip Blackburn -- Breakage, turnover, and betting market efficiency: new evidence from Japanese horse tracks / W. David Walls and Kelly Busche -- The impact of tipster information on bookmakers' prices in UK horse-race markets / Michael A. Smith -- On the marginal impact of information and arbitrage / Adi Schnytzer, Yuval Shilony and Richard Thorne -- Covarianace decompositions and betting markets: early insights using data from French trotting / Jack Dowie -- A competitive horse-race handicapping algorithm based on analysis of covariance / David Edelman -- Efficiency in the handicap and index betting markets for English rugby league / Robert Simmons, David Forrest and Anthony Curran -- Efficiency of the over-under betting market for National Football League games / Joseph Golec and Maurry Tamarkin -- Player injuries and price responses in the point spread wagering market / Raymond D. Sauer -- Is the UK National Lottery experiencing lottery fatigue? / Stephen Creigh-Tyte and Lisa Farrell -- Time-series modelling of Lotto demand / David Forrest -- Reconsidering the economic impact of Indian casino gambling / Gary C. Anders -- Investigating betting behaviour: a critical discussion of alternative methodological approaches / Alistair Bruce and Johnnie Johnson -- The demand for gambling: a review / David Paton, Donald S. Siegel and Leighton Vaughan Williams.
Includes bibliographical references and index.
gau 23/01/14
Loans
Keywords: Gambling; Gambling -- Economic aspects